Perancangan Desain Antarmuka Aplikasi Learning Management System (LMS) Lembaga Kursus Dan Pelatihan (LKP) - Abdul Aziz, Riyan; Moch. Hari Purwidiantoro; Sri Widiyanti (Politeknik Aceh, 2025)
Learning Management System (LMS) is an approach to applying computer technology in education. This approach allows students to learn freely anytime and anywhere via the internet, which contains various sources of information. This study aims to create a Learning Management System (LMS) application interface design model specifically for Course and Training Institutions (LKP), making it easier for LKP to choose and manage online classes according to their needs. The research method used in designing the LKP LMS application interface design is the keep it simple, stupid (KISS) method. The results of creating the interface with a high-fidelity version include the website's main page, the register page, the login page, the admin page, the tutor page, and the student page. The results of the calculation using the system usability scale (SUS) obtained an average of 82.92, the acceptability range is in an acceptable status, the grace scale is included in the B scale, and the adjective ratings are included in the excellent category.